A fixed point method in quasistatic rate-type viscoplasticity - Djabi, Saddik; Sofonea, Mircea (Zielona Góra: Uniwersytet Zielonogórski)
Two initial and boundary value problems describing the quasistatic evolution of semilinear rate-type viscoplastic models with/without internal state variables are considered. The existence and uniqueness of the solution is proved using only classical existence and uniqueness results for linear elasticity followed by a fixed point technique.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka